In Vitro Cytotoxic Activity Test of Tampa Badak (Voacanga foetida (Blume) Leaves on L1210 Leukemia - Susanty, Adriani (Fakultas Farmasi Universitas Andalas, 2021)
The Voacanga foetida (Blume) Rolfe leaves have cytotoxic activity based on our previous research, namely the Brine Shrimps Lethality Test on ethanol extract. This study tested the anticancer activity of the extract and leaf fraction of Voacanga foetida in vitro on L1210 leukemia cells using the direct cell count method and doxorubicin positive control. The results showed that the methanol extract, butanol, ethyl acetate, and hexane fractions, as well as isolated compounds Tb1, Tb2, and Tb3 leaves from Voacanga foetida, had IC50 values of 4.4; 9; 8.4; 16.8; 0.9; 1.8; and 1.1 ppm, compared with doxorubicin with an IC50 value of 0.2 ppm. Based on the IC50 value, it showed that the extract, fraction and isolated compounds of Voacanga foetida had a strong cytotoxic effect, as evidenced by the IC50 value < 30 ppm for each test concentration.